The Role of Self-Efficacy in Career Adaptability: A Comparative Study of Senior and Vocational High School Students - Rizki Amalia; Muhammad Syarif Hidayatullah (Research, Training and Philanthropy Institution Natural Aceh, 2026)
Career development during adolescence requires psychological resources that enable students to manage educational and occupational transitions. However, empirical evidence comparing self-efficacy and career adaptability across academic and vocational secondary education remains limited. This study examined the relationship between self-efficacy and career adaptability, compared these variables between senior high school (SMA) and vocational high school (SMK) students, and assessed the contribution of self-efficacy to career adaptability. A quantitative cross-sectional survey was conducted with 224 Indonesian secondary school students recruited through convenience sampling, with participant recruitment exhibiting snowball characteristics. Data were collected using the General Self-Efficacy Scale (GSES) and the Career Adapt-Abilities Scale (CAAS) and analyzed using descriptive statistics, Pearson correlation, independent-samples t-test, and simple linear regression. Self-efficacy was positively associated with career adaptability (r = 0.824, p < 0.001) and explained 67.8% of its variance (R² = 0.678, p < 0.001). Vocational high school students demonstrated significantly higher self-efficacy and career adaptability than senior high school students. These findings highlight the importance of strengthening self-efficacy through school-based career guidance interventions.